2014
DOI: 10.1111/clr.12485
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate long‐term clinical performance of dental implants placed in sites with a previous early implant failure: a retrospective analysis

Abstract: Within the limits of the present study, early implant failure was not an obstacle for implant replacement at the same site after an adequate soft and hard tissues healing period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 33 publications
(53 reference statements)
2
56
0
1
Order By: Relevance
“…The surface characteristics of implants were not considered in three studies . In only two studies, the implants with SLA surface characteristics were definitely used in both the initial implantations and the reimplantations. Regrettably, no statistical comparison between SLA and other surface characteristics was evaluated in any of the available studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface characteristics of implants were not considered in three studies . In only two studies, the implants with SLA surface characteristics were definitely used in both the initial implantations and the reimplantations. Regrettably, no statistical comparison between SLA and other surface characteristics was evaluated in any of the available studies.…”
Section: Discussionmentioning
confidence: 99%
“…The surface characteristics of implants were not considered in three studies. 27,45,48 In only two studies, 44,46 the implants with SLA surface characteristics were definitely used in both the initial implantations and the reimplantations.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement implants were followed for less than 1 year in two studies, 23,25 and for at least 1 year in seven studies. 18,19,20,21,10,27,24 In of one study, the observation period of replacement implants was not reported 26 (Table 2).…”
Section: Implants Placed At Sites With History Of One Implant Failurementioning
confidence: 99%
“…Nonetheless, implant replacement still represents a challenging scenario. 18 Although a number of retrospective cohort studies 18,19,20,21,10,22,23,24,25,26 and one prospective clinical trial 27 have evaluated survival rates of implants placed at sites with history of implant failure, these studies included limited numbers of patients. As such, the precise prognosis of implants placed at failed sites remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since preliminary studies of the osseointegration process, dental implants have been widely used for the rehabilitation of partially or completely edentulous patients over time with high survival rates (Kwon et al 2014;Wang et al 2015;Tenenbaum et al 2016), and represent one of the most important therapeutic advances in modern dentistry (Wilson et al 2016). Despite the high success and survival rates reported for a large number of clinical studies, implant failure has been frequently reported (Laine et al 2005;Yamane et al 2013;Belibasakis et al 2015).…”
mentioning
confidence: 99%